Efektivitas Penggunaan Worksheet Terhadap Peningkatan Kemampuan Mengenal dan Membentuk Huruf Bagi Anak Disgrafia - Riskiatul Mawardah; Muhammad Musyaddad; Masri’ah (Universitas Muria Kudus, 2025)
One aspect of language skills that is very important in learning and student success in participating in school is writing ability. However, nowadays, many students are found to have difficulty writing (dysgraphia). To overcome the problem of dysgraphia in children, researchers used teaching materials in the form of LKPD (Learning Worksheets) containing worksheets designed for children with dysgraphia to practice writing. This study used a mixed method, where this study combines qualitative and quantitative research. Qualitative data collection was obtained through interviews and observations related to children with dysgraphia. Meanwhile, quantitative data collection was obtained through questionnaires given to the subject's homeroom teacher to measure the effectiveness of LKPD designed for children with dysgraphia in improving their understanding of recognizing and forming letters of the alphabet. From the results of interviews and observations, it can be seen that the subject experienced writing difficulties due to a lack of literacy introduction in the home environment, a lack of interest in reading from the subject, and hereditary factors from the subject's parents. From the results of the questionnaire assessment conducted by the subject's homeroom teacher (a child with dysgraphia), it can be seen that the analysis score for the student's understanding development aspect obtained a score of 25 points with a percentage of 72% which is in the category of Developing as expected.